Joe Watkins and Mary Graham Moore, 1958. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 9-3-58 p.16.
Joe Watkins and Mary Graham Moore, 1958. They are in Salem Square, to perform at a Salem Band concert.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth